2020
DOI: 10.1021/jacs.0c09753
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Designed Redox-Active Au(I) N-Heterocyclic Carbene: An Immunogenic Cell Death Inducer

Abstract: Immunogenic cell death (ICD) is a way of reengaging the tumor-specific immune system. ICD can be induced by treatment with chemotherapeutics. However, only a limited number of drugs and other treatment modalities have been shown to elicit the biomarker responses characteristic of ICD and to provide an anticancer benefit in vivo. Here, we report a rationally designed redox-active Au­(I) bis-N-heterocyclic carbene that induces ICD both in vitro and in vivo. This work benefits from a synthetic pathway that allows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 38 publications
0
75
0
2
Order By: Relevance
“…Accumulating studies have combined nanoparticles with immunoadjuvants, chemotherapeutics, photodynamic therapy, or again photothermal therapy in order to reshape the tumor hypoxic microenvironment to elicit or enhance ICD (81,82). These novel nanoparticles synergized with IR and enhanced antitumor immune function (83)(84)(85)(86)(87). Qian Chen et al confirmed that PLGA-R837@Cat nanoparticle-based x-ray radiation inhibited primary tumors significantly in comparison with RT alone.…”
Section: The Methods Of Enhancing Ir-induced Icdmentioning
confidence: 99%
“…Accumulating studies have combined nanoparticles with immunoadjuvants, chemotherapeutics, photodynamic therapy, or again photothermal therapy in order to reshape the tumor hypoxic microenvironment to elicit or enhance ICD (81,82). These novel nanoparticles synergized with IR and enhanced antitumor immune function (83)(84)(85)(86)(87). Qian Chen et al confirmed that PLGA-R837@Cat nanoparticle-based x-ray radiation inhibited primary tumors significantly in comparison with RT alone.…”
Section: The Methods Of Enhancing Ir-induced Icdmentioning
confidence: 99%
“…In 2021, Arambula et al 58 reported a rationally designed redox-active Au( i ) bis N-heterocyclic carbene (NHC) compound 2.13 (Fig. 19A) that can induce ICD both in vitro and in vivo .…”
Section: Metal Based Complexes As Icd Inducersmentioning
confidence: 99%
“…Fourth, co-loading multi-components on nanoparticles could significantly improve ICD and anti-tumor effect. Sen et al engineered a redox-active Au(I) bis-N-heterocyclic carbine (Au(I) bis-NHC) that realized the double effect combining TrxR2 inhibition (damaging biological antioxidants) with increased oxidative stress [ 80 ]. The combination of photodynamic therapy with oxygen therapy based on C@HPOC showed enhanced specific CD8 + T cell response and abscopal effect [ 66 ].…”
Section: Improving Tumor Immunogenicitymentioning
confidence: 99%